If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15t + 4 = 48 Reorder the terms: 4 + 15t = 48 Solving 4 + 15t = 48 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 15t = 48 + -4 Combine like terms: 4 + -4 = 0 0 + 15t = 48 + -4 15t = 48 + -4 Combine like terms: 48 + -4 = 44 15t = 44 Divide each side by '15'. t = 2.933333333 Simplifying t = 2.933333333
| 9p^2-12p-5=0 | | 10+x=3x-6(5-3x) | | 3.7n-9.2=-10+3.9 | | -1.86t^2+15t+25=0 | | |3p+7|=4 | | 2x^2-5bx+4cx-10bc=0 | | 65x+50=45x+95 | | 9.6x-6.6=-10.9+5.3x | | 5-(-16)+3(16)= | | x+4+x+x/2=44 | | 12+10+5+3= | | 12+10+5= | | 1000*1000=1000*1000 | | -3x+7=x-1 | | 2-4x=6x+72 | | 0.5(2t+8)=4+6t | | 15+4y=7y-13 | | -5*3=15-7c | | 100000000*10000000= | | 9-.66x=-1 | | 9(3-2y)+8y=-23 | | -18=-3x+7x-6 | | one-one= | | -6x-22=-8x-16 | | 2(x+5)(x-2)=x(x+5)+190 | | 4g+4(g-2)=-5(g-4)-g | | 5(3+3x)-1=29 | | 6+-1= | | a+(a+4)=(a+5)-(a-1) | | -8x+3x^2-11=0 | | 7+-2= | | 3(7x+6)=144 |